2017
DOI: 10.1136/acupmed-2016-011137
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Attenuates Hyperglycaemia and Improves Ovarian Function in Female Rats Subjected to Continuous Light Exposure

Abstract: Objective Exposure to unnatural light cycles is increasingly associated with obesity and the metabolic syndrome. The purpose of this study was to examine the effects of electroacupuncture (EA) on glucose metabolism and ovarian function in female rats subjected to longterm continuous light exposure. Methods Female Sprague-Dawley rats (n=24) were divided into three experimental groups: an LD group that was maintained under a normal light-dark cycle (healthy control); an LL group that was exposed to continuous li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Several studies have shown that women exposed to night-light shifts had irregular menstrual cycles (Lawson et al, 2011) that were frequently associated with dysmenorrhea and metabolic syndrome (Lim et al, 2018), insulin resistance, and deregulation of glucose metabolism (Sharma et al, 2017), all of which are recognized risk factors for PCOS (Ali, 2015). Prolonged light exposure was reported to induce polycystic ovaries and hyperandrogenism in rodents as well (Kang et al, 2015(Kang et al, , 2017Paixão et al, 2017), indicating the relationship between circadian rhythm disorder and manifestation of PCOS. However, the effect of circadian rhythm disruption on reproductive hallmarks of PCOS and the mechanism underlying this pathogenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that women exposed to night-light shifts had irregular menstrual cycles (Lawson et al, 2011) that were frequently associated with dysmenorrhea and metabolic syndrome (Lim et al, 2018), insulin resistance, and deregulation of glucose metabolism (Sharma et al, 2017), all of which are recognized risk factors for PCOS (Ali, 2015). Prolonged light exposure was reported to induce polycystic ovaries and hyperandrogenism in rodents as well (Kang et al, 2015(Kang et al, , 2017Paixão et al, 2017), indicating the relationship between circadian rhythm disorder and manifestation of PCOS. However, the effect of circadian rhythm disruption on reproductive hallmarks of PCOS and the mechanism underlying this pathogenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies in the field of reproductive medicine showed that transcutaneous electrical acupoint stimulation (TEAS) might provide an important methodology for restoring ovarian function [1114]. TEAS is a noninvasive treatment combining acupuncture point stimulation with electrical stimulation, which is easily acceptable for patients who are afraid of the pain and topical skin tissue injury caused by acupuncture.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture, which has been used to treat diseases for more than 2500 years in China [ 21 ], has become increasingly popular worldwide in recent years for its convenience and low incidence of adverse effects. Acupuncture is widely applied in clinical practice for treating PCOS [ 19 ], and studies have concluded that acupuncture is effective against metabolic disturbances associated with IR such as overweight [ 22 ], hyperglycemia [ 23 , 24 ], and hyperlipidemia [ 25 ] by improving insulin sensitivity [ 26 ]. It has also been reported that acupuncture may improve glycemic outcomes in women with PCOS [ 27 ].…”
Section: Introductionmentioning
confidence: 99%